Human 2.0 : reimagining HR in the age of transhumanism (Emerald Publishing Limited, 2026)
Human 2.0: Reimagining HR in the Age of Transhumanism explores the transformative effects of transhumanist technologies, such as AI, biotechnology, and neuro-enhancements, on the field of human resources (HR). As technological advances blur the boundaries between human and machine, HR professionals find themselves at a pivotal juncture, where traditional workforce models must evolve to remain relevant. This edited collection provides a comprehensive analysis of how these emerging technologies will reshape HR practices, presenting a future-oriented view of a workplace enriched by innovations that amplify human capability and efficiency. Addressing the imperative for ethical new HR paradigms, Human 2.0 bridges theory and practice through case studies and data-driven insights. Key topics include the integration of AI and machine learning into HR processes, the role of biotechnology in enhancing employee wellness and productivity, and the potential of neuro-enhancements to foster cognitive development. This forward-looking guide serves both as an academic resource and a practical toolkit, empowering HR professionals to navigate and harness technological advancements for a competitive advantage in a rapidly evolving landscape.